Socio-economic Governance in the EU - Orosz, Ágnes; Szijártó, Norbert (Public Governance, Administration and Finances Law Review, 2022)
This paper focuses on the complexity of socio-economic governance in the European Union. We define socio-economic governance as the process of governing societies in a situation where no single actor can claim absolute dominance thus socio-economic governance is the outcome of the interaction between European Union institutions (European Union decision-makers) and member states (national policy-makers). Since the onset of the global financial crisis and the euro crisis a decade ago, social issues have become substantially prominent in EU governance and policy debate. Furthermore, the Covid-19 crisis brought again social issues to the fore. There is no dedicated social governance framework in the European Union but there are several mechanisms (strategies, initiatives and regulations) through which social governance is practiced. At the same time, the framework for European economic governance has substantially been strengthened as a consequence of the global financial crisis and the euro crisis and can be characterised by a matured but incomplete framework. On the one hand, this paper aims to collect and investigate all governance tools related to economic and social issues in the European Union, and on the other hand, this research examines the impacts of those governance tools on member states.